Development of alginate-montmorillonite-starch with encapsulated Trichoderma harzianum and evaluation of conidia shelf life - Adzmi, Fariz; Musa, Mohamed Hanafi; Siddiqui, Yasmeen; Wong, Mui Yun; Abdul Hamid, Hazandy; Abdu, Arifin; Abiri, Rambod (Friends Science Publishers, 2021)
Biological control agents, such as Trichoderma harzianum, are widely used in sustainable agriculture. However, commercialisation and mass production of biocontrol products have remained a challenge, especially in viability and efficiency in field application. The encapsulation method has emerged as a sophisticated technique to develop the formulation of T. harzianum. Hence, encapsulation through extrusion was used to prepare T. harzianum beads. The physical characteristics comprising weight, diameter, and swelling ability of the beads were significantly improved when the starch percentage was increased. Alginate-montmorillonite-starch (10%) revealed the lowest shrinkage and the highest swelling ability. The interaction within the functional groups of alginate, montmorillonite, and starch was confirmed by the Fourier-transform infrared spectroscopic (FTIR) study. Furthermore, scanning electron microscopic analysis exposed compatible scattering of montmorillonite particles and starch granules over the alginate linkages. Meanwhile, the X-ray diffraction analysis confirmed the exfoliation between starch and montmorillonite. Storage of T. harzianum beads at 5°C was more suitable than storage at 28°C. At low temperature, the encapsulated T. harzianum beads maintained their viability at 6.59 ± 0.12 log CFU g−1 for an effective threshold value for up to seven months. The current findings indicated that the combination of alginate, montmorillonite, and starch is the best formulation of encapsulated T. harzianum with improved conidia shelf life.